From Frictionless to Thoughtless: The Correlation between Seamless UI/UX and Impulsive Buying Behavior in Digital Payment Apps - Suandana, Ni Putu Widantari; Kherismawati, Ni Putu Eka (TECHNOVATE: Journal of Information Technology and Strategic Innovation Management, 2025)
The evolution of financial technology has shifted the focus of payment system design from security to "frictionless" experiences. While seamless UI/UX (User Interface/User Experience) enhances efficiency, it inadvertently minimizes the cognitive deliberation required in purchasing decisions. This study aims to investigate how the seamless design of digital payment apps correlates with impulsive buying behavior among Generation Z. Using a descriptive quantitative method with 30 undergraduate students, this research analyzes user interaction patterns and spending habits. The findings reveal a critical correlation: the reduction of transaction barriers (such as one-click checkout and biometric login) significantly lowers the psychological threshold for spending. 65% of respondents admitted that the speed of transaction prevents them from reconsidering unnecessary purchases, leading to a "thoughtless" buying state. The study concludes that while "frictionless" design optimizes convenience, it acts as a catalyst for hedonic consumption by bypassing the rational evaluation process known as System 2 thinking.